INOVASI SOSIO-PEDAGOGIS DALAM PENDIDIKAN KESEHATAN: IMPLEMENTASI PERILAKU HIDUP BERSIH DAN SEHAT MELALUI POJOK LIFE SKILL DAN HEALTHCARE - Dewi Roso Wulan; Dheva Yudistira Maulana; Zahra Aliya Diah Widuri; Indah Tri Utami; Isna Dhella Yasya; Levy Martdiana Andika; Yuda Riptanto; Astrid Febriyanti Manurung; Desriyan Shandra Naufalista; Naufal Marta Lestari; et al. (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Clean and Healthy Living Behavior (PHBS) remains a challenge among children in Indonesia. Early educational interventions have been proven effective in increasing students' knowledge and skills in practicing hygienic behaviors, especially through innovative and contextual health education approaches. This study developed the Life Skill and Healthcare Corner as an interactive socio-pedagogical educational medium to instill health values sustainably within the school environment. Activities were carried out at SDN 4 Kendalrejo and SMP Tri Bhakti Tegaldlimo using participatory education methods and hands-on practice. Through this approach, students not only gain a conceptual understanding of PHBS but also demonstrate changes in attitudes and behaviors toward healthy living habits. These findings indicate that the Life Skill and Healthcare Corner is effective as a socio-pedagogical innovation in strengthening health education in elementary and secondary schools.